2021
DOI: 10.46222/ajhtl.19770720-158
|View full text |Cite
|
Sign up to set email alerts
|

Making “Sense” of the Middle of the Pyramid Consumer’s Dining Experience

Abstract: It is assumed that fine-dining creates immersive experiences that could enhance the flavour of a meal or dish by leveraging a combination of multi-sensory stimuli. An exploratory hybrid-study identified multi-sensory dining experience stimuli from scientific literature, namely visual (eyes), haptic (touch), taste, olfactory (smell), auditory (hearing), and design and layout that affect restaurant choice. The purpose of this study was to investigate the important multi-sensory stimuli in the dining experience o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The importance of creating a unique and memorable experience for customers rather than simply meeting their basic expectations means that restaurants must pay attention to all these elements to create a positive and memorable dining experience for their customers (Namin 2017). The dining experience is influenced by various factors such as food, service, atmosphere, value, and the overall ambience of the restaurant (Kleinhans et al 2016). Some scholars who studied the quality factors of the dining experience, for example, the casual dining experience, indicated that the casual dining experience has four dimensions, namely, food aspects, interaction quality, physical environment, and service outcome (Hussein 2018), and customer satisfaction with the dining experience was positively correlated with the willingness to extend the experience (El-Said et al 2021).…”
Section: Dining Experiencementioning
confidence: 99%
“…The importance of creating a unique and memorable experience for customers rather than simply meeting their basic expectations means that restaurants must pay attention to all these elements to create a positive and memorable dining experience for their customers (Namin 2017). The dining experience is influenced by various factors such as food, service, atmosphere, value, and the overall ambience of the restaurant (Kleinhans et al 2016). Some scholars who studied the quality factors of the dining experience, for example, the casual dining experience, indicated that the casual dining experience has four dimensions, namely, food aspects, interaction quality, physical environment, and service outcome (Hussein 2018), and customer satisfaction with the dining experience was positively correlated with the willingness to extend the experience (El-Said et al 2021).…”
Section: Dining Experiencementioning
confidence: 99%
“…Massive literature has been dedicated to understanding the components and consequences of dining experience, due to its crucial role in the restaurant business (Marinkovic et al, 2014). Kleinhans et al (2016) pointed out that dining experience dimensions have changed over the last few years. The initially popular dining experience factors were tangibles, responsiveness, reliability, assurance and empathy.…”
Section: Dining Experience Customer Satisfaction and Revisit Intentionmentioning
confidence: 99%
“…, 2014). Kleinhans et al. (2016) pointed out that dining experience dimensions have changed over the last few years.…”
Section: Literature Reviewmentioning
confidence: 99%